Sense of control and wellbeing decades after exposure to blue asbestos at Wittenoom, Western Australia - Reid, Alison; Alfonso, Helman; Ti, J.; Wong, E.; de Klerk, N.; Musk, A. (2012)
Objective: The objective of this study was to examine the impact of the knowledge of past asbestos exposure on psychosocial health. Methods: Blue asbestos was mined and milled at Wittenoom in Western Australia between 1943 and 1966. In 2007, SF-12 and Locus of Control (LOC) questionnaires were sent to 5,101 surviving Wittenoom workers and residents. Wellbeing scores and LOC scores were then examined in relation to quantitative exposure measures using linear regression. Results: Wellbeing scores were lower among Wittenoom workers and residents compared with the Western Australian population, although an exposure-response relationship with cumulative asbestos exposure was not found. Those who arrived in Wittenoom as children had a more external sense of control than those who arrived there as adults. There was a 0.12 increase in LOC with a 2.7-fold increase in cumulative asbestos exposure (f/ml-years) (P<0.01). Conclusions: The study concluded that asbestos operation at Wittenoom may have had a detrimental impact on former workers' and residents' sense of control over their lives. © W. S. Maney & Son Ltd 2012.